AN INNOVATIVE APPROACH TO EVALUATE THE BEHAVIOUR OF VERTICALLY LOADED PILE GROUPS BASED ON ELASTIC THEORY - M. Cao; L. Z. Chen; S. L. Chen (Lowland Technology International, 2007)
An efficient analytical approach is proposed to calculate the settlement of a pile group under vertical loads. The proposed approach is based on the superposition of the displacement of individual pile. In the superposition calculation, an interaction factor, which was determined using the technique by Muki and Sternberg, is employed to facilitate the analysis of pile groups subjected to static vertical loads. The proposed interaction factor can consider the strengthening effect of intervening piles. The solution of the proposed approach is compared with other existing solutions. Their difference in estimating the behaviour of pile groups is investigated. Finally, numerical examples on two pile groups are presented to discuss the influence of dimensionless pile and soil parameters on the behaviour of pile groups. The results show that the proposed approach gives a more reasonable analysis on pile groups.